Analysis of the Effects of Intercity Flows on Land Use Changes outside the Urban Boundaries; Case study: Lands around the communication roads of the cities of Babol, Ghaem Shahr and Sari (تحقیقات کاربردی علوم جغرافیایی)
This research tends to analyze and assess the impact of intercity flows rate on land use changes around the community roads of the cities of Babol, Ghaem Shahr and Sari. This research is descriptive-analytic and performed in quantitative method. A wide range of techniques including gravity model, flow analysis model, entropy analysis and GIS software environment were applied for performing required analysis. Research findings show that increase in passenger transfer and cargo transit in the community roads of the cities of Babol, Ghaem Shahr and Sari, resulted in increase in applications for land use changes around these roads; of course, the impact of passenger transfer (with correlation coefficient of 0.72) was higher than cargo transit (with correlation coefficient of 0.43). Concerning their existing interactions and multicenter of the studied area (based on entropy analysis), codification of control system and integrated spatial management is hereby suggested in form of a comprehensive urban plan toward supervising and managing land use changes in suburban areas of the aforesaid cities.